The Role of Emotions in the Context of Shaping the Attitudes of Academic Teachers Towards E-Learning - Tuczyński, Krystian (International Journal of Research in E-learning, 2022)
The article attempts to identify emotions displayed by university teachers towards the adoption of e-learning solutions in the academic environment. The article is divided into four main parts. Part one is a description of one of the key components of human attitude, which is emotions. The second part describes the research methodology and defines the original research tool, which was used to measure the emotions manifested by academic staff in the use of e-learning. The third part is the analysis of the research results, which presents detailed summaries of each aspect of e-learning. The final section summarizes the research findings and makes recommendations for higher education institutions in the field of distance learning in an the academic community.